A validated HPLC method for the assay of xanthone and 3-methoxyxanthone in PLGA nanocapsules - Teixeira, M (2003)
This work relates the development and validation of a simple reversed-phase high-performance liquid chromatographic (HPLC) method for the analysis of xanthone (XAN) and 3-methoxyxanthone (3-MeOXAN) in poly(D,L-lactide-co-glycolide) (PLGA) nanocapsule formulations. This method does not require any complex sample extraction procedure. Chromatographic separation is made with a reversed-phase C18 column, using methanol-water (90:10, v/v) as a mobile phase at a flow rate of 1 mL/min. Identification is made by UV detection at 237 nm. The isocratic system operates at ambient temperature and requires 7 min of chromatographic time. The developed method is statistically validated according to United States Pharmacopoeia 25 and International Conference on Harmonization guidelines for its specificity, linearity, accuracy, and precision. The assay method proposed in this study is specific for XAN and 3-MeOXAN in the presence of nanocapsule excipients. Diode-array analyses confirm the homogeneity of XAN and 3-MeOXAN peaks in stressed conditions. Standard curves are linear (r > 0.999) over the concentration range of 0.4-2.5 and 1.0-5.8 g/mL for XAN and 3-MeOXAN, respectively. Recovery from nanocapsules ranges from 99.6% to 102.8% for XAN and 98.8% to 102.4% for 3-MeOXAN. Repeatability (intra-assay precision) is acceptable with relative standard deviation values of 1.2% for XAN and 0.3% for 3-MeOXAN.